Digital Technologies in Construction Engineering Selected Papers - Klyuev, Sergey Vasil'yevich.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book gathers the latest advances, innovations, and applications in the field of construction engineering, as presented by researchers and engineers at the Digital Technologies in Construction Engineering conference, held in Belgorod, Russia, on June 8-9, 2021. It covers highly diverse topics, including industrial and civil construction, building materials; environmental engineering and protection; sustainability; structure safety and special construction structures. The contributions, which were selected by means of a rigorous international peer-review process, highlight numerous exciting ideas that will spur novel research directions and foster multidisciplinary collaborations. .
Chapter 1: Mohr-Coulomb Models for Dynamic Analysis of Granular Metamaterials in Earthquake Engineering -- Chapter 2: Distribution of the Mixed Bulk Components after Impact on the Baffle Plane -- Chapter 3: Impact of PMB Preparation Technology on the Properties of Road Composites -- Chapter 4: Physical-Chemical Aspects of Modifying Cement Systems with Individual and Complex Plasticizing Admixtures.
Keywords: Buildings -- Design and construction; Environmental management; Urban economics; Cultural property; Building Construction and Design; Environmental Management; Urban Economics; Cultural Heritage; Civil engineering -- Congresses; Construction industry -- Technological innovations -- Congresses; Structural engineering -- Congresses